1999
DOI: 10.1021/es980659t
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of 2,4-Dichlorophenoxyacetic Acid by Model Particles Simulating Naturally Occurring Soil Colloids

Abstract: Binary and ternary model particles containing montmorillonite, ferrihydrite, and humic acid (HA) were used to determine the changes in the sorption behavior of the herbicide 2,4-D (2,4-dichlorophenoxyacetic acid) upon the interassociation of these three major soil constituents. On single sorbents, 2,4-D sorption was high with S-type isotherms on ferrihydrite, moderate with L-type isotherms on HA, and zero on montmorillonite. In binary sorbents, ferrihydrite and humic acid coatings on montmorillonite provided s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 41 publications
8
83
0
1
Order By: Relevance
“…Although soil organic carbon content had the greatest overall influence on 2,4-D sorption in the B horizon, very little of the sorption could be accounted for by this property or any of the other soil properties. The presence of iron oxides is known to increase 2,4-D sorption in soil (Reddy and Gambrell 1987;Celis et al 1999), and were visually observed as rust flecks in B horizon soil samples, but not quantitatively measured. It is generally accepted that as soil organic carbon content decreases with soil depth, other soil properties play an increasingly important role in 2,4-D sorption (Reddy and Gambrell 1987;Green and Karickhoff 1990;Wauchope et al 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Although soil organic carbon content had the greatest overall influence on 2,4-D sorption in the B horizon, very little of the sorption could be accounted for by this property or any of the other soil properties. The presence of iron oxides is known to increase 2,4-D sorption in soil (Reddy and Gambrell 1987;Celis et al 1999), and were visually observed as rust flecks in B horizon soil samples, but not quantitatively measured. It is generally accepted that as soil organic carbon content decreases with soil depth, other soil properties play an increasingly important role in 2,4-D sorption (Reddy and Gambrell 1987;Green and Karickhoff 1990;Wauchope et al 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Others have used FTIR to investigate the interaction of anionic herbicides and herbicide degradation products with metal oxides to determine the types of complexes and structures formed upon adsorption. Celis et al (1999) and Goyne et al (2004) investigated mechanisms of 2,4-dichlorophenoxyacetic acid (2,4-D) sorption to metal oxide surfaces using transmission FTIR and ATR-FTIR, respectively. Both interpreted the acquired spectra as indication that 2,4-D sorbed to variable charge mineral surfaces via electrostatic interaction between the carboxylate group and ^Metal-OH 2 + surface functional groups on Al and Fe oxides.…”
Section: Herbicides and Pharmaceuticalsmentioning
confidence: 99%
“…S-type isotherms are commonly observed for the sorption of polar pesticides on polar surfaces from water, particularly when the pesticide also contains a hydrophobic moiety that may result in hydrophobic intermolecular attraction between adjacent pesticide molecules in the sorbed state [27,[38][39][40]. Such intermolecular attractions are favored at higher surface coverages, thus explaining the enhanced sorption at higher fungicide concentrations (cooperative sorption) characteristic of S-type isotherms [38].…”
Section: Sorption Of Metalaxyl On Soil From Racemic and Non-racemic Imentioning
confidence: 99%